(untitled) (Orchid Insights: A Multidisciplinary Journal of Orchid College, 2025)
This study examines the impact of liquidity analysis on the profitability of Nabil Bank Limited over a five years period (2018/19–2022/23). Liquidity management is critical for financial institutions as it ensures operational stability while maintaining profitability. This research employs key liquidity indicators such as the Current Ratio, Quick Ratio and Loan-to-Deposit used to measure profitability. The findings reveal that Nabil Bank maintains a strong liquidity position, with an average current ratio of 2.36 and an LDR of 84.96%, indicating effective liquidity management. However, the study identifies a negative correlation between liquidity and profitability, as both ROA and ROE exhibit a declining trend over the study period. While higher liquidity enhances short-term financial stability, excessive liquidity may hinder profitability by limiting investment opportunities. The study suggests that an optimal balance between liquidity and profitability is essential for long-term financial sustainability. Given the study’s reliance on secondary data and a limited timeframe, future research should incorporate primary data and a broader sample to enhance the findings.